2012
DOI: 10.1021/np300009w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phospholipid-Based Formulations of Boswellia serrata Extract on the Solubility, Permeability, and Absorption of the Individual Boswellic Acid Constituents Present

Abstract: Boswellia serrata gum resin extracts are used widely for the treatment of inflammatory diseases. However, very low concentrations in the plasma and brain were observed for the boswellic acids (1-6, the active constituents of B. serrata). The present study investigated the effect of phospholipids alone and in combination with common co-surfactants (e.g., Tween 80, vitamin E-TPGS, pluronic f127) on the solubility of 1-6 in physiologically relevant media and on the permeability in the Caco-2 cell model. Because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Several pilot clinical trials suggest promising beneficial therapeutic effects with no serious, long-term, or irreversible adverse effects [114] but some minor adverse effects such as diarrhoea, abdominal pain and nausea [115,116]. A study deals with the evaluation and assessment of the safety/toxic potential of B. serrata indicated that B. serrata is relatively safe in rat up to the dose of 500 mg/kg B.wt [117].…”
Section: Identification Of Boswellia Speciesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several pilot clinical trials suggest promising beneficial therapeutic effects with no serious, long-term, or irreversible adverse effects [114] but some minor adverse effects such as diarrhoea, abdominal pain and nausea [115,116]. A study deals with the evaluation and assessment of the safety/toxic potential of B. serrata indicated that B. serrata is relatively safe in rat up to the dose of 500 mg/kg B.wt [117].…”
Section: Identification Of Boswellia Speciesmentioning
confidence: 99%
“…However, a major limitation is the low systemic absorption in rodents and humans of BAs, especially of the major active compounds (1–4) (16–17), which have been evidenced by pharmacokinetic studies [120,121]. For example, the plasma and brain concentrations of BAs were found to be very low following oral administration of even high B. serrata doses [114]. In general, AKβ-BA (4) was not detected at all [38] while β-BA (1) and Aβ-BA (2) achieved pharmacologically relevant concentrations in plasma [114].…”
Section: Identification Of Boswellia Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…the one used in this study, in a 1:1:1 (w/w/w) formulation of BE:lecithin:pluronic f127 (co-surfactant) mixed at a 1:1 ratio with microcrystalline cellulose [20]. When compared to Casperome™ on equimolar basis, this formulation led to roughly 1.5-fold higher mean plasma levels for KBA, AKBA and βBA, as well as higher mean brain levels for βBA (roughly 10-fold).…”
Section: Discussionmentioning
confidence: 99%